The role of let-7b in the inhibition of hepatic stellate cell activation by rSjP40. - Xiaolei Sun; Li Zhang; Yuting Jiang; Aihong Li; Dandan Zhu; Jiangrong Wu; Yinong Duan (Public Library of Science (PLoS), 2021)
Background Hepatic stellate cells (HSCs) are one of the main cell types involved in liver fibrosis induced by many factors, including schistosomes. Previous studies in our lab have shown that recombinant P40 protein from Schistosoma japonicum (rSjP40) can inhibit HSC activation in vitro. Let-7b is a member of the let-7 microRNA family and plays an inhibitory role in a variety of diseases and inflammatory conditions. In this study, we investigated the role of let-7b in the inhibition of HSC activation by rSjP40. Methods Expression of let-7b was detected by quantitative real-time PCR. A dual luciferase assay was used to confirm direct interaction between let-7b and collagen I. We also used western blot to assess protein levels of TGFβRI and collagen type I α1 (COL1A1). Results We found that rSjP40 up-regulates expression of let-7b in HSCs. Let-7b inhibits collagen I expression by directly targeting the 3'UTR region of the collagen I gene. Furthermore, we discovered that let-7b inhibitor partially restores the loss of collagen I expression caused by rSjP40. Conclusion Our research clarifies the role of let-7b in the inhibition of HSC activation by rSjP40 and will provide new insights and ideas for the inhibition of HSC activation and treatment of liver fibrosis.